ANALISIS YURIDIS JASA DEBT COLLECTOR DALAM PENARIKAN OBJEK SENGKETA OLEH PERUSAHAAN PEMBIAYAAN - NIM. A1012221138, MUHAMMAD FARID HIBATULLAH AMZAR (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Motorcycle financing begins with the borrower selecting a motorcycle at a showroom, making a down payment, and then the showroom contacts the financing company. The financing company then conducts a credit assessment of the borrower's eligibility, and upon approval, the company will pay the remaining balance to the showroom. The borrower then makes periodic installment payments to the financing company. To collect delinquent installments, financing companies typically involve a third party, a debt collector. The relationship between the financing company, the borrower, and the debt collector is regulated by law, where the financing company (creditor) grants the debt collector (third party) the power to collect the debt based on the initial agreement and the power of attorney. The research question is: